Cities between economic and social developments. Relationships and possible outcomes. - Kempen, Ronald van (TH Zürich, NSL, 2009)
Der Beitrag stellt eine kritische Literaturauswertung dar, mit der der Frage nachgegangen wird, wie sich der Zusammenhang von ökonomischen, sozialen und räumlichen Entwicklungen auf der Ebene der Stadt darstellt. Stichworte sind dabei die Städtekonkurrenz, die Wettbewerbsfähigkeit von Städten und die Rolle der weichen Standortfaktoren, soziale Polarisierung und Ungleichheit, soziale und räumliche Disparität, die Bedeutung wirtschaftlicher und sozialer Kohäsion. Zum Schluss fragt der Autor nach den Möglichkeiten, mit Hilfe von local governance-Konzepten zu gewünschten wirtschaftlichen und gesellschaftlichen Ergebnissen in den Städten zu kommen.

The paper focuses on the complex relationship between economic and social developments in cities. While cities increasingly strive to be strong in both, the relationship between the economic and social aspects is often far from clear. Conclusions put forward about this relationship are often no more than assertions and are seldom based on empirical research. The intricacy of the relationship implies an intricate governance structure; without collaboration between the different sectors and stakeholders, governing a city would seem to be impossible. The following question is addressed in the paper: How are the economic, social, and spatial developments in cities related to each other? The question is answered on the basis of a critical review of the relevant literature. At the end of the paper, a brief discussion of the extent to which governance arrangements can lead to favorable outcomes of economic and social processes is to be found.
Keywords: Stadtentwicklungsplanung; Wirtschaftsentwicklung; Stadtforschung; Lebensbedingungen; Standort; Standortfaktor; Forschungsprojekt; Globalisierung; Wettbewerbsfähigkeit; Metropolregion; Metropole; Städtewettbewerb; Weicher Standortfaktor; Kohäsion; Soziale Ungleichheit; Local Governance; Stadtentwicklungspolitik